Pengelolaan Hutan Berbasis Kearifan Lokal pada Masyarakat Hukum Adat Mororene Hukaea Laea di Bombana Sulawesi Tenggara - Heryanti, Heryanti (Asosiasi Pengajar Hukum Adat (APHA) Indonesia, Fakultas Hukum Universitas Trisakti - Jakarta Barat, Indonesia, 2018)
The development of the era with the inclusion of the new patterns of patterens influencing the pattern of people’s lives from traditional to modern society incarnated in the form of prismatic society New patterns in the form of technology, modernity or capitalism also often influence patterns of life costumary law communities that always try to exist or maintain the value of their local wisdom such as in forest resource management patterns in tradition values due to the presumption that these patterns effective and inefficient. During this time community’s habits referred to as local wisdom have only become a binding force for the community groups in their interaction with nature. The attachment of costumary law communities to nature was realized with the sustainability of forest forests in the area of costumary law communities.